L’engoulevent ou l’étrangeté porteuse de malheur (Nord du Cameroun) - Christian Seignobos (Revue d'ethnoécologie)
In its features and behaviours, long-tailed nightjar (Caprimulgus climacurus) is a bird like no other. It indeed intrigues by such dissimilarities and frightens Man by flying off at his approach. The interpretation of this dangerousness links with human beings in what is most sensitive to them: their own reproduction. Long-tailed nightjar is renowned for making yet-to-be-born children die, as well as those who come into the world.Various rituals seek to check the series of newborn deaths in one same family. Often singularly complex, they start off with collective bird hunting. The child thereby preserved is given an apotropaic name at birth: “engoulevent” (long-tailed nightjar in French). These rituals are yet very vivacious in the Mandara mounts and their piedmonts. As for mission enthusiasts and the islamicised, they are very careful not to touch long-tailed nightjar, while claiming to no longer believe therein. This infra-belief tallying with linguistic families and even the pagan/Muslim break raises the issue of its production area, its centre and its margins. How was it built? By competing with other evil animals accused of generating the same evils? Would it likely be historicised?